Linaria yusufeliensis, a replacement name for the Turkish Linaria turcica Makbul & Hamzaoğlu (Plantaginaceae) - Galán De Mera, Antonio; Makbul, Serdar; Hamzaoğlu, Ergi̇n (Phytotaxa, 2018)
Linaria Miller (1754: without page) is currently included in the Plantaginaceae family. This genus consists of ca. 150 species mainly distributed in Europe, Northern Africa and Central and Western Asia, but introduced and naturalized in other regions of the world with temperate climate (Sáez & Bernal 2009). It comprises annual or perennial herbs, with flowering and non-flowering shoots. The flowers occur in bracteate racemes and have a zygomorphic corolla with a long spur, and the lower petal closing the corolla throat; winged or wingless seeds are produced in their pods (Rocio et al. 1999).